2007
DOI: 10.1086/510438
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variants in the Promoter Region of Chitinase 3–Like 1 (CHI3L1) and Susceptibility to Schizophrenia

Abstract: The chitinase 3-like 1 gene (CHI3L1) is abnormally expressed in the hippocampus of subjects with schizophrenia and may be involved in the cellular response to various environmental events that are reported to increase the risk of schizophrenia. Here, we provide evidence that the functional variants at the CHI3L1 locus influence the genetic risk of schizophrenia. First, using case-control and transmission/disequilibrium-test (TDT) methodologies, we detected a significant association between schizophrenia and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 31 publications
6
62
2
Order By: Relevance
“…Indeed, plasma concentrations of YKL-40 are partly heritable (10 ) and the rs4950928, a single nucleotide polymorphism in the proximal promoter of CHI3L1, accounts for 9% of its variance (10 ). Mechanistically, MYC/ MAX transcriptional factors do not bind well to the minor allele of rs4950928 (11 ), which decreases CHI3L1 transcription (12 ) and consequently plasma YKL-40 concentrations (13)(14)(15).…”
mentioning
confidence: 99%
“…Indeed, plasma concentrations of YKL-40 are partly heritable (10 ) and the rs4950928, a single nucleotide polymorphism in the proximal promoter of CHI3L1, accounts for 9% of its variance (10 ). Mechanistically, MYC/ MAX transcriptional factors do not bind well to the minor allele of rs4950928 (11 ), which decreases CHI3L1 transcription (12 ) and consequently plasma YKL-40 concentrations (13)(14)(15).…”
mentioning
confidence: 99%
“…At the same time, many different genome-wide association studies have demonstrated that the different SNPs in the promoter region of the CHI3L1 gene are linked to the circulating CHI3L1 levels [40,41], but it was unclear whether the CHI3L1 SNPs could affect its expression levels. With this question, we determined the plasma CHI3L1 levels in AD patients and healthy controls with different genotypes of these three SNPs and found that the carriers with the variant genotype CG+GG of rs4950928 had lower plasma CHI3L1 levels, whereas the presence of the rs10399931 CT+TT genotype enhanced apparently plasma CHI3L1 when compared with the corresponding CC genotype carriers, and no significant differences were discovered between rs6691378 genotypes and CHI3L1 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike AMCase and chitotriosidase, HC-gp39 lost its chitin-binding domain and distributed the binding sites in the carbohydrate-binding groove, so we suggested that the other 10 sites we identified are related to the function of binding carbohydrate. Recent research has also implicated the CHI3L1 gene in susceptibility to schizophrenia (Zhao et al 2007). …”
Section: Discussionmentioning
confidence: 99%